Determinants of Islamic Social Reporting on Sharia Commercial Banks of Indonesia - Ikbar Luqyana; Dilla Saezana Zunaidi (Journal of Business & Banking, 2021)
This paper intends to confirm the effect of profitability, leverage, sharia compliance, firm size and investment account holders on the disclosure of Islamic Social Reporting. So that practitioners, academics and the public can fully understand the accountability and full disclosure of Islamic commercial banks based on sharia. This paper applies legitimacy theory to developed the hypotheses linking between ISR and the determinants (profitability, leverage, sharia compliance, firm size and investment account holders). Purposive sampling technique was used in the selection of research samples. The sample obtained is twelve Islamic banks that can be studied as a sample. Classical assumption test, multiple linear regression, f test, R2 test, and t-test were used in this study. This paper finds that the level of ISR disclosure is still low (59.5%). We also find that Islamic Social Reporting disclosure is affected by profitability, firm size and investment account holders. Meanwhile, the disclosure of Islamic Social Reporting is not affected by leverage and sharia compliance.